Factors Associated with Spirituality in Patient Undergoing Hemodialysis - Panma, Yuanita (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Aims: Chronic Kidney Disease (CKD) is a global health burden, with hemodialysis being a critical yet life-altering therapy. Spirituality has emerged as an essential dimension influencing the well-being of patients undergoing hemodialysis. However, there is limited understanding of the factors associated with spirituality among Indonesian patients, necessitating culturally sensitive research. Objective: This study aimed to identify factors associated with spirituality in patients undergoing hemodialysis in Indonesia. Methods: A cross-sectional study was conducted in Jakarta's hemodialysis unit in 2017, involving 148 participants selected through consecutive sampling. Data were collected using validated instruments, including the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT Sp12), the Beck Depression Inventory (BDI), the Medical Outcomes Study-Social Support Survey (MOS-SSS), and the Kidney Disease Quality of Life Short Form (KDQOL-SF36). Data were analyzed using univariate, bivariate, and multivariate logistic regression. Results: The majority of participants were female (52%), married (76.3%), and unemployed (75%), with an average age of 54.86 years. Half of the participants exhibited high spiritual levels (50.7%). Social support (OR = 1.052, p < 0.001) and depression (p < 0.05) were significantly associated with spirituality. Other variables, including HD frequency, duration of HD, and burden of kidney disease, were identified as confounders. Conclusion: Social support and depression significantly influence the spiritual well-being of hemodialysis patients, highlighting the need for comprehensive care approaches that address social and mental health alongside spiritual needs. Tailored interventions, including family-centered and spiritual counseling, can improve the quality of life for these patients.